The effect of acetic acid-induced pain in parkinson’s disease model in zebrafish - ALTURFAN, EBRU IŞIK (My University, 2023)
Parkinson's disease (PD) is the second most common neurodegenerative disease caused by the degeneration of dopaminergic neurons and the accumulation of Lewy bodies. Pain is one of the most common non-motor symptoms in PD, but the molecular mechanism of pain in PD is not fully understood, which prevents early diagnosis of PD. We aimed to determine the changes in opioidergic pathways when external pain is inflicted by inducing pain intraperitoneally in zebrafish, for which we generated a rotenone-induced PD model. After behavioural analyses in control(C), acetic acid (AA), rotenone (ROT), and rotenone+ acetic acid (ROT+AA) groups, catecholamine levels in brain tissue were determined by LC-MS/MS, expression of opioid peptides and their receptors by RT-PCR, expression of tyrosine hydroxylase by immunohistochemical method, and analyses of oxidant-antioxidant parameters by spectrophotometric methods. In the ROT group, distance travelled, average speed, and brain dopamine levels decreased, while LPO (lipid peroxidation) and NO (nitric oxide) increased as indicators of oxidative damage, and the SOD activity decreased. The mRNA expression of lrrk, pink1, and park7 genes associated with PD increased, while the mRNA expression of park2 decreased. This indicates that rotenone exposure is a suitable means to induce PD in zebrafish. The fact that body curvature was higher in the AA group than in the ROT and ROT+AA groups, as well as the decreased expression of penka, pdyn, and ion channels associated with the perception of peripheral pain in the ROT+AA group, suggest that mechanisms associated with pain are impaired in the rotenone-induced PD model in zebrafish.
Keywords: Yaşam Bilimleri; Biyokimya; Sağlık Bilimleri; Temel Bilimler; Life Sciences; Biochemistry; Health Sciences; Natural Sciences; Klinik Tıp (MED); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Doğa Bilimleri Genel; Biyoloji ve Biyokimya; ÇOK DİSİPLİNLİ BİLİMLER; BİYOKİMYASAL ARAŞTIRMA YÖNTEMLERİ; Clinical Medicine (MED); Natural Sciences (SCI); Life Sciences (LIFE); NATURAL SCIENCES, GENERAL; BIOLOGY & BIOCHEMISTRY; MULTIDISCIPLINARY SCIENCES; BIOCHEMICAL RESEARCH METHODS; Multidisipliner; Multidisciplinary; pain; behaviour; opioids; Parkinson disease; zebrafish